IMPACTOS E DESAFIOS ASSOCIADOS COM A IMPLANTAÇÃO DA NORMA DE DESEMPENHO EM EDIFICAÇÕES PREDIAIS - Belém, Karla; Starling, Cícero; Andery, Paulo (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The present work aims to presenting an exploratory study regarding the ABNT NBR 15575/2013 in housing projects, focusing on the design process management. The research was carried out using structured interview and short case studies. The results point out that some significative changes were introduced in the design process: disciplines integration, early introduction of consultant activities in the feasibility and schematic design studies, as well as the use of checklist and design review procedures during design stages.